1984
DOI: 10.1113/jphysiol.1984.sp015345
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long‐term high‐frequency stimulation on capillary density and fibre types in rabbit fast muscles.

Abstract: SUMMARY1. Rabbit fast muscles (tibialis anterior, t.a.; extensor digitorum longus, e.d.l.; and peroneal muscles) were stimulated for up to 28 days by electrodes implanted in the vicinity of the lateral popliteal (peroneal) nerve for 8 h/day, using either intermittent high-frequency (three trains at 40 Hz/min, each 5 s duration), or continuous stimulation at 10 Hz. This did not result in muscle hypertrophy even after 28 days.2. Capillary density (number of capillaries/mm2) was increased in e.d.l. from 251 ± 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0
8

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 30 publications
4
28
0
8
Order By: Relevance
“…85.5 Although it is not possible to compare directly results from different species and stimulation regimes, Brown et al (1976) also reported the absence of capillary growth in rabbit muscles using 40 Hz for 4 days, but with a different pattern of stimulation (3 ² 5 s bouts min¢ for 8 h per day) and supramaximal voltage (which activates all muscle fibres). However, using the same stimulation pattern Hudlick a & Tyler (1984) found an increased capillary supply after 14 days. Increases in capillary supply preceding the changes in oxidative enzymes were described previously (Pette et al 1973;Brown et al 1976), and were confirmed more recently (Skorjanc et al 1998) using different stimulation regimes than those used in the present study.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…85.5 Although it is not possible to compare directly results from different species and stimulation regimes, Brown et al (1976) also reported the absence of capillary growth in rabbit muscles using 40 Hz for 4 days, but with a different pattern of stimulation (3 ² 5 s bouts min¢ for 8 h per day) and supramaximal voltage (which activates all muscle fibres). However, using the same stimulation pattern Hudlick a & Tyler (1984) found an increased capillary supply after 14 days. Increases in capillary supply preceding the changes in oxidative enzymes were described previously (Pette et al 1973;Brown et al 1976), and were confirmed more recently (Skorjanc et al 1998) using different stimulation regimes than those used in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…Using different frequencies of stimulation, similar changes in both enzyme pattern and capillary supply were observed after more intensive stimulation for 14 days (Reichmann et al 1985). Increases in resistance to fatigue induced by various patterns of repetitive muscle stimulation were associated with a greater capacity for oxidative metabolism, involving a coordinated increase in the activities of enzymes from â-oxidation of fatty acids, the citric acid cycle, and terminal substrate oxidation in the respiratory chain (Pette et al 1975;Hudlick a et al 1984;Reichmann et al 1985Reichmann et al , 1991. The increase in the activity of oxidative enzymes was accompanied by a marked decrease in the enzyme activities of the glycolytic pathways (Simoneau & Pette, 1988), thus strengthening the argument that the capacity for sustained activity of skeletal muscle correlates directly with aerobic metabolic capacity and indirectly with anaerobic metabolic capacity.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations